Prevention and promotion is the cornerstone in the effort to erradicate cholera in primary care - Yurieth Gallardo; Ruber Gallardo (Medwave, 2013)
Introduction. Cholera has accompanied mankind since time immemorial with historical records from China, India and ancient Greece. However, registers are available only since 1817, when the first documented pandemic emerged in Asia and spread to Turkey and Arab countries. Since then, eight episodes of cholera pandemic have occurred in the world. Objective. To inform the scientific community about the epidemiological situation in the province of Granma, Cuba, at the cross-sectional period of July 2012 and the prevention and health promotion measures that were introduced in the first level of care for cases of diarrhea caused by Vibrio cholerae. These measures were implemented in the territory with an intersectoral approach, resulting in the adoption of healthy lifestyles by the general population. Conclusion. Basic sanitation activities were undertaken to slow the spread of the disease, complemented by suggestions to the medical community about the importance of epidemiological surveillance to detect reemergence.